Pengaruh Kecerdasan Emosional (EQ) Terhadap Prestasi Belajar Pendidikan Jasmani Pada Siswa Kelas XI di SMA Negeri 2 Semarang (Universitas Negeri Semarang, 2021)
Many argue that learning achievement requires intellectual intelligence, but in several research studies it is explained that intellectual intelligence is not a major factor in achieving learning achievement, there is another factor, namely emotional intelligence (EQ). This study aims to determine the effect of emotional intelligence (EQ) on learning achievement of physical education in class XI students at SMA Negeri 2 Semarang. This research is a research quantitative research model: case study design. Emotional intelligence data (X) uses online questionnaires and physical education learning achievement data is obtained through the learning outcomes of class XI in the odd semester of the 2020/2021 school year. The data analysis used a sample of 208 students with clustered sampling technique. Data analysis using SPSS 21 software with simple linear regression test.The regression equation Y = 90.490 + -0.017 explains that every 1% increase in the value of emotional intelligence (EQ), the value of learning achievement increases -0.017. Based on the significance value, the value obtained is 0.352> 0.05 from the probability value, so it can be concluded that there is no effect of emotional intelligence (EQ) on learning achievement of physical education.It can be concluded that emotional intelligence (X) has no effect on learning achievement (Y) of physical education class XI at SMA Negeri 2 Semarang.